Politics of Quality in Education: A Comparative Study of Brazil, China and Russia - Kauko; Jaakko; Risto Rinne; Tuomas Takala (Routledge, 2022)
The question of quality has become one of the most important framing factors in education and has been of growing interest to international organisations and national policymakers for decades. Politics of Quality in Education focuses on Brazil, China, and Russia, part of the so-called emerging nations’ BRICS block, and draws on a four-year project to develop a new theoretical and methodological approach.
The book builds a comparative, sociohistorical, and transnational understanding of political relations in education, with a particular focus on the policies and practices of Quality Assurance and Evaluation (QAE). Tracking QAE processes from international organisations to individual schools, contributors analyse how QAE changes the dynamics in the roles of state, expertise, and governance. The book demonstrates how national and sub-national actors play a central role in the adaptation, modification or rejection of transnational policies.